2003
DOI: 10.1097/00002820-200310000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Mammograms and Pap Smears for Australian Deaf Women

Abstract: This study aimed to assess baseline knowledge about mammograms and Pap smears among Australian Deaf women, to investigate their participation in breast and cervical cancer screening services, and to explore, where relevant, their perceptions about their access to breast and cervical screening services. An interview schedule was developed, and a convenience sample of 13 Deaf women was interviewed face-to-face by the first researcher with an accredited Auslan interpreter. The Deaf women's knowledge about mammogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…With poor prose literacy levels and general lack of accessible health information, Deaf individuals struggle with lower “fund of health knowledge” (R. Pollard, 1998) and have reported poor health knowledge in preventive, cardiovascular, cancer, and sexual health (Heuttel & Rothstein, 2001; Margellos-Anast et al, 2006; Peinkofer, 1994; Tamaskar et al, 2000; Wollin & Elder, 2003; Woodroffe et al, 1998). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With poor prose literacy levels and general lack of accessible health information, Deaf individuals struggle with lower “fund of health knowledge” (R. Pollard, 1998) and have reported poor health knowledge in preventive, cardiovascular, cancer, and sexual health (Heuttel & Rothstein, 2001; Margellos-Anast et al, 2006; Peinkofer, 1994; Tamaskar et al, 2000; Wollin & Elder, 2003; Woodroffe et al, 1998). …”
Section: Discussionmentioning
confidence: 99%
“…This likely results in a lower general health knowledge (Heuttel & Rothstein, 2001; Peinkofer, 1994; Tamaskar et al, 2000; Wollin & Elder, 2003; Woodroffe, Gorenflo, Meador, & Zazove, 1998; Zazove, 2009), along with existing health disparities (Barnett, 1999; Barnett, Klein, et al, 2011; McKee, Barnett, et al, 2011) in the Deaf population. Deaf ASL users rely on a visual language that does not have a written form.…”
mentioning
confidence: 99%
“…Our community-campus partnership (Moores University of California San Diego Cancer Center, Deaf Community Services of San Diego Inc., Bovee Productions, and Gallaudet University) began creating cancer education videos in American Sign Language (ASL) with open captioning and easy-to-understand graphics to facilitate the acquisition of cancer knowledge within the Deaf community [5–10]. A study conducted by Choe and colleagues concluded that cervical cancer knowledge was increased among Deaf women who viewed the partnership’s ASL cervical cancer educational video [5].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, health literacy (Pollard & Barnett, 2009), mental health (Steinberg, Sullivan, and Loew 1998), and specific health conditions including cancers (Folkins et al, 2005;Orsi et al, 2007;Sacks et al, 2013;Steinberg et al, 2002;Wollin & Elder, 2003) A comparative approach to examining the health knowledge of people living with hearing loss or deafness was also evident in the health knowledge research (e.g., Kleinig & Mohay, 1990;Margellos-Anast et al, 2006;Pollard & Barnett, 2009). However, the researchers consistently concluded and discussed the need for health knowledge to be taught and delivered in formats (e.g., sign language, through interpreters) that are more accessible to people who communicate via visual languages.…”
Section: Health Knowledgementioning
confidence: 99%
“…However, the researchers consistently concluded and discussed the need for health knowledge to be taught and delivered in formats (e.g., sign language, through interpreters) that are more accessible to people who communicate via visual languages. They also discussed the need for (hearing) health professionals to be more aware of Deaf culture and the communication needs of people living with hearing loss or deafness (e.g., Margellos-Anast et al, 2006;Steinberg et al, 1998Steinberg et al, , 2002Wollin & Elder, 2003). It should be noted however, that the researchers rarely noted or considered in their research papers the barriers (e.g., cost, time off work, availability of workshops) that health professionals face when attempting to implement their recommendations, who is responsible for driving/overseeing the implantation of these recommendations.…”
Section: Health Knowledgementioning
confidence: 99%